Approved budget: 2002 fiscal year - Federal Republic of Nigeria; Federal republic of Nigeria (Lagos : The federal government press, 2002)
This book is the 2002 fiscal year approved budget of the federal government of Nigeria.
Title from cover: 2002 fiscal year
asm; 23/01/2019
Arch
Keywords: Budget; Nigeria